Procedural Aspects Regarding References for Preliminary Rulings - Oana-Măriuca Petrescu (Romanian Journal of European Affairs, 2008)
The purpose of preliminary rulings, or the preliminary reference as it is known, can be traced directly to the need to secure uniformity in the Community legal order throughout the Member States. The procedure of preliminary rulings was mentioned for the first time by the Advocate General Joseph-Louis Lagrange 40 years ago in this Opinion in Bosch v de Geus case. Much of the responsibility for applying the rules laid down in the European Community Treaty (EC Treaty) and in Community acts belongs to the national courts of the Member States. To help safeguard the uniform application of Community law, article 234 (former art.177) of EC Treaty, therefore lays down a procedure which enables national courts to refer to the European Court of Justice questions of Community law that they have to decide before giving a judgment.